Architecture of the caudal vena cava wall of the dog at the level of the liver caudate lobe - Medeiros de Mello, Josiane; Orsi, Antonio Marcos [UNESP]; Piffer, Carlos Roberto [UNESP]; Torrejais, Márcia Miranda (My University, 2000)
The vascular segment of the caudal vena cava of the dog at the level of the caudate lobe was shown to be intimately related to hepatic tissue through the hepatic capsule and parenchyma. The tunica adventitia of the caudal vena cava was formed mainly by smooth muscle cells with collagen and elastic fibers arranged in bundles. The thin tunica media of the vein was also formed by smooth muscle cells, collagen and elastic fibers arranged in bundles. The tunica intima presented an elastic sub-endothelial network. The hepatic segment of the caudal vena cava showed a myoconnective architecture and propulsive characteristics in terms of its hemodynamic pattern.
Keywords: Caudal vena cava; Dog; Liver caudate lobe; Microscopy; Vascular architecture; Venous wall; adventitia; animal tissue; cava vein; dog; elastic fiber; functional anatomy; hemodynamics; intima; liver parenchyma; microvasculature; nonhuman; smooth muscle fiber; ultrastructure; vascular smooth muscle; Animals; Dogs; Hemodynamic Processes; Liver; Muscle, Smooth, Vascular; Vena Cava, Inferior; Animalia; Canis familiaris